The etiology and differential diagnosis of “autoimmune hepatitis-like liver disease” in children: a single-center retrospective study - Ma, Di; Liu, Xinglou; Ai, Guo; Pan, Wen; Liu, Lingling; Huang, Yuan; Liao, Yi; Lu, Yuanyuan; Zhang, Zhan; Zhou, Hua; Huang, Zhihua; Hao, Xingjie; et al. (Frontiers in Pediatrics, 2024)
Background: Children with autoimmune hepatitis (AIH) often present with symptoms similar to those of other liver diseases. This study consists of a comparison between the clinical and histological characteristics of AIH and those of other four AIH-like liver diseases (i.e., drug-induced liver injury (DILI), gene deficiency, infectious liver disease and other etiology of liver disease), as well as an evaluation of the AIH scoring system's diagnostic performance. Methods: Children's cases that met the diagnostic criteria for AIH-like liver disease at our center from January 2013 to December 2022 were included. The clinical and histological characteristics of the AIH group were retrospectively analyzed and compared with those of the other four groups. Results: A total of 208 cases were included and divided into AIH group (18 cases), DILI group (38 cases), gene deficiency group (44 cases), infectious liver disease group (74 cases), and other etiology group (34 cases). The antinuclear antibodies (ANA)≥1:320 rate was significantly higher in the AIH compared to the other four groups after multiple testing correction (p<0.0125), while positive cases of antibodies to liver-kidney microsomal-1(anti-LKM1, n=3) and smooth muscle antibodies (SMA, n=2) were only observed in the AIH group. The positive rates of antibodies to liver cytosol type1(anti-LC1) and Ro52 were higher than those in the other four groups. The serum immunoglobulin G (IgG) and globulin levels, as well as the proportions of portal lymphoplasmacytic infiltration, lobular hepatitis with more than moderate interface hepatitis, and lobular hepatitis with lymphoplasmacytic infiltration, were significantly higher in the AIH group than in the other four groups after multiple testing correction (p<0.0125). The cirrhosis rate in the AIH group was higher than that in the DILI and infectious liver disease groups (p<0.0125). Both the simplified (AUC>0.73) and the revised systems (AUC>0.93) for AIH have good diagnostic performance, with the latter being superior (p<0.05).Positive autoantibodies (ANA ≥ 1:320 or anti-LKM1 positive, or accompanied by SMA, anti-LC1 or Ro-52 positive) and elevated serum IgG or globulin levels contribute to early recognition of AIH. The presence of lobular hepatitis with more than moderate interface hepatitis and lymphoplasmacytic infiltration contribute to AIH diagnosis.